Class S: appropriation of ‘lesbian’ subculture in modern Japanese literature and New Wave cinema - Shamoon, Deborah (Cultural Studies, 2021)
In the 1920s in Japan, girls attending single-sex secondary schools developed a girls’ culture (shōjo bunka) or subculture to insulate themselves temporarily from the pressures of patriarchal society. Part of this subculture was a practice called s kankei (s or sister relationships), also called Class S, which were same-sex romantic attachments between classmates, condoned at the time as a temporary practice relationship that would end upon graduation, followed by an arranged marriage. Although s relationships were not ‘lesbian’ in the contemporary sense, literature and film created by men in the 1920s through the 1960s appropriated aspects of girls’ culture, including exploitative representation of female homosexuality. One example is Manji (Quicksand, 1928) by Tanizaki Jun’ichirō, which depicts an s relationship as lurid and perverse. Kawabata Yasunari plagiarized from his female disciple Nakazato Tsuneko in order to publish the most popular Class S novel of the era, Otome no minato (Harbor of Girls, 1937). Kawabata also included exploitative scenes of female homosexuality in his novel Utsukushisa to kanashimi to (Beauty and Sadness, 1963). Both Tanizaki’s and Kawabata’s novels were made into films by New Wave directors, Manji in 1964 by Masumura Yasuzō and Beauty and Sadness in 1965 by Shinoda Masahiro, and featured the first depictions of ‘lesbianism’ in Japanese film. Although these films reinscribe the male gaze, they helped inspire a nascent gay culture and opened the way for more authentic gay cinema. This essay recenters girls’ culture in modern Japanese literature and film, and discusses the variable meaning of female homosexuality for different audiences.
Keywords: approches et analyses; arts; asie; discipline; discours dominant; japon; patriarcat; personnes lesbiennes; ressource en ligne; régions géographiques; systèmes d'oppressions; études culturelles; études littéraires

Sémi: roman - Shimazaki, Aki (Domaine français, 2021)
« Après plus de quarante ans de mariage, Tetsuo et Fujiko se sont installés en maison de retraite car Fujiko, atteinte de la maladie d’Alzheimer, requiert une prise en charge particulière. Un matin, au réveil, elle ne reconnaît plus son époux. D’abord en grand désarroi, Tetsuo entreprend finalement de reconquérir celle qui le prend désormais pour un étranger auquel elle se trouve simplement fiancée. »-- Site de l'éditeur
Keywords: arts; asie; care; cours; discipline; japon; lit2815; premier cycle; roman; régions géographiques; thématiques; écriture des femmes*; études littéraires